Testing the convergent and discriminant validity of the Decisional Balance Scale of the Transtheoretical Model using the Multi-Trait Multi-Method approach. - Guo, B; Aveyard, P; Fielding, A; Sutton, S (2008)
The authors extended research on the construct validity of the Decisional Balance Scale for smoking in adolescence by testing its convergent and discriminant validity. Hierarchical confirmatory factor analysis multi-trait multi-method approach (HCFA MTMM) was used with data from 2,334 UK adolescents, both smokers and non-smokers. They completed computerized and paper versions of the questionnaire on 3 occasions over 2 years. The results indicated a 3-factor solution; Social Pros, Coping Pros, and Cons fit the data best. The HCFA MTMM model fit the data well, with correlated methods and correlated trait factors. Subsequent testing confirmed discriminant validity between the factors and convergent validity of both methods of administering the questionnaire. There was, however, clear evidence of a method effect, which may have arisen due to different response formats or may be a function of the method of presentation. Taken with other data, there is strong evidence for construct validity of Decisional Balance for smoking in adolescence, but evidence of predictive validity is required.